Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/maec.12725
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variability of the coastal ocean stratification in the Gulf of Naples: Two decades of monitoring the marine ecosystem at the LTERMC site, between land and open Mediterranean Sea

Abstract: Coastal areas represent ∼ 17 % of marine primary production (Smith et al., 2005), contribute to the largest portion of fish catches (∼ 80 % if we consider all Large Marine Ecosystems as coastal systems, Sherman et al., 2009), and provides for more than 90% of the global trade (WTO, 2018). While the latter is sustained by the crucial role of maritime transportation, the former strongly depend on physical processes that occur in coastal systems. Winds, runoff, tides, and heat fluxes (Ferrari & Wunsch, 2009) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 102 publications
2
21
0
Order By: Relevance
“…Notwithstanding the strong environmental variability characterizing the study area, robust seasonal signals were observed not only in the temperature and salinity data, as previously reported (Kokoszka, Le Roux, et al, 2022; Ribera d'Alcalà et al, 2004), but also for nutrients and Chl a .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Notwithstanding the strong environmental variability characterizing the study area, robust seasonal signals were observed not only in the temperature and salinity data, as previously reported (Kokoszka, Le Roux, et al, 2022; Ribera d'Alcalà et al, 2004), but also for nutrients and Chl a .…”
Section: Discussionsupporting
confidence: 84%
“…The maximum nutrient concentrations at the surface are generally observed in February–May, in conjunction with the annual maxima of freshwater inputs (Kokoszka, Le Roux, et al, 2022) while the highest Chl a concentration occurs toward the end of this period (April–May), when the stratification increases, as observed in other temperate ecosystems (Cloern & Jassby, 2008; Lavigne et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…At LTER-MC the decrease in copepod richness is associated with rare species, which have been consistently found at very low frequencies (<1%) in recent years. The increased abundance of species that typically live in offshore and epi-mesopelagic waters has likely been favored by the enhanced coupling between inshore and offshore waters over the last few years (Kokoszka et al, 2023).…”
Section: Over a Longer Time Scale Copepod Richness In The Mediterraneanmentioning
confidence: 99%
“…The mixed layer depth (MLD), which identifies the vertical extension of the homogeneous surface layer, was calculated from in situ density profiles following the method of de Boyer Montégut et al (2004). Further methodological details related to MLD are reported in Kokoszka et al (2023).…”
Section: Sampling and Sample Treatmentmentioning
confidence: 99%